Changes in body mass, stature and BMI in South African elite U18 Rugby players from different racial groups from 2002-2012 - Durandt, J.; Green, M.; Masimla, H.; Lambert, M. (Journal of Sports Sciences, 2018)
The purpose of this study was to determine whether there are differences between racial groups for body mass, stature and body mass index (BMI) in South African elite U18 rugby players and whether there were significant changes in these measurements between 2002 and 2012. Self-reported body mass and stature were obtained from U18 players (n = 4007) who attended the national tournament during this period. BMI was calculated for each player.White players were 9.8 kg heavier than black players, who were 2.3 kg heavier than coloured players (P < 0.0001). The body mass of all groups increased from 2002 to 2012 (P < 0.0001). White players were 7.0 cm taller than black players who were 0.5 cm taller than coloured players (P < 0.0001). Players` stature measurements did not change significantly during the study period. The average BMI of white players was 0.9 kg·m-2 greater than black players who were on average 0.7 kg·m-2 greater than coloured players (P < 0.0001). The BMI of all groups changed similarly over the study period. The body mass, stature and BMI of elite under-18 rugby players in South Africa were significantly different between racial groups. This has implications for transforming the game to make it representative of the South African population.